THE EFFECT OF CORPORATE GOVERNANCE MECHANISM AND ACCOUNTING CONSERVATIONS ON TAX AVOIDANCE - Trisusanti, Dianita; Lasdi, Lodovicus (Research In Management and Accounting (RIMA), 2018)
Law number 17 about State Finances in Article 11 states that the income of the country consists of tax revenue, non-tax revenue, and grants. From year to year the Indonesian government has always increase revenue target of taxation sector. On the side of the taxpayer (company), tax paid to the government will be recognized as an expense, which in turn tax will reduce the amount of net profit of the company. The company believes that tax evasion provide substantial economic benefits and un-expensive sources of financing. The purpose of this study was to examine and analyze whether the corporate government mechanism (institutional ownership concentration, the percentage of independent board, the number of commissioners, the number of audit committee, and quality audits) and accounting conservatism take effect on tax avoidance. This research is a quantitative research with the object of research is manufacturing companies listed in Indonesia Stock Exchange from 2010 to 2013. Data were obtained from the publication of the audited financial statements or annual reports by IDX and book of ICMD. Sampling in this study used purposive random sampling. Data analysis techniques used in this research is regression analysis Ordinary Least Square (OLS). The results showed that the corporate governance mechanism influence on tax avoidance. Three of five proxy mechanism of corporate governance have significant effect on tax avoidance, those three proxies are institutional ownership, number of board of directors, and audit committees, while two other proxy are the percentage of independent board and audit quality which have un-significant effect on tax avoidance